Red berry snail Sphaerassiminea miniata (Gastropoda: Mollusca) and its potential as a bioindicator of environmental health in mangrove ecosystem of Pomalaa, Kolaka District, Indonesia - MUHAMMAD FAJAR PURNAMA; SLAMET B. PRAYITNO; MAX R. MUSKANANFOLA; SURYANTI SURYANTI (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Purnama MF, Prayitno SB, Muskananfola MR, Suryanti. 2024. Red berry snail Sphaerassiminea miniata (Gastropoda: Mollusca) and its potential as a bioindicator of environmental health in mangrove ecosystem of Pomalaa, Kolaka District, Indonesia. Biodiversitas 25: 2330-2339. Sphaerassiminea miniata Habe 1942 has a high sensitivity to environmental changes in mangrove forest areas. Its existence can be confirmed when the overall condition of the mangrove ecosystem is in good condition. The aim of this research is to analyze the density and distribution of the S. miniata gastropod population in relation to the density status of mangroves in the reference site area and overburden exposure areas. This research adopted a purposive sampling method for determining research stations, a simple random sampling technique for placing stations or distributing sampling points (sub-stations), and a hand-picking method for technical sampling of S. miniata in the field. The results showed that the mangrove density at each station was very dense (3,700-6,000 trees/ha), the population density of S. miniata ranged from 8.67-38.33 ind./m2, and the distribution pattern of S. miniata at each station was clumped with a Morishita index (Id) value range of 1.28-1.34. Sphaerassiminea miniata was found at all stations in the reference site area (Totobo mangrove ecosystem). No individual was found in the area with overburden exposure (Dawi-Dawi mangrove ecosystem). Changes in the environmental tone in the Dawi-Dawi mangrove ecosystem, especially the substrate area through the input of sediment waste (overburden), which has been going on for a long time and continuously (until now), directly degrades the living space of the S. miniata population on the ground floor (benthos) of the waters. The vulnerability of this species to environmental changes makes it a limiting factor in the quality of habitat health in mangrove ecosystems (Bioindicators).